2014
DOI: 10.1002/jbm.a.35039
|View full text |Cite
|
Sign up to set email alerts
|

Definitive endoderm differentiation of human-induced pluripotent stem cells using signaling molecules and IDE1 in three-dimensional polymer scaffold

Abstract: Human-induced pluripotent stem cells (hiPSCs) are considered to be potentially able to differentiate into all human cell lineages and thus hold promise as an unlimited source for cell replacement therapies in clinical applications. Definitive endoderm (DE) formation is the first and crucial step in the development of visceral organs such as liver, lung, pancreas and so forth. Therefore, efficient generation of DE cells ensures the efficient generation of eventual target cells used in cell therapy. In the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 59 publications
(140 reference statements)
3
28
1
Order By: Relevance
“…In comparison to 2D culture systems, 3D culture improves islet like morphology, differentiation, and function. These results correspond with the previous findings of the studies on the types of stem cells (Aloysious & Nair, ; Hoveizi et al, ; Khorsandi, Khodadadi, Nejad‐Dehbashi, & Saremy, ). The role of hADSCs in tissue engineering and regenerative medicine is promising; however, bioartificial pancreas based on tissue engineering still appears to be fantastic.…”
Section: Discussionsupporting
confidence: 92%
“…In comparison to 2D culture systems, 3D culture improves islet like morphology, differentiation, and function. These results correspond with the previous findings of the studies on the types of stem cells (Aloysious & Nair, ; Hoveizi et al, ; Khorsandi, Khodadadi, Nejad‐Dehbashi, & Saremy, ). The role of hADSCs in tissue engineering and regenerative medicine is promising; however, bioartificial pancreas based on tissue engineering still appears to be fantastic.…”
Section: Discussionsupporting
confidence: 92%
“…19,20 Electrospun nanofibrous scaffolds possess many unique properties, including extremely high surface-to-volume ratio, appropriate porosity, and malleability to conform to a wide variety of sizes and shapes which are similar to the ECM and can enhance the adhesion, proliferation and growth of cells. 2,4 Previous findings from many other researchers were consistent with ours, which also demonstrated that the nanoarchitecture of the scaffold has significant effects on various cell behaviors including cell adhesion, orientation and proliferation. [21][22][23] Here, although we found that hiPSCs can be cultured on electrospun and film scaffolds but we repeatedly found significantly better performance of hiPSCs on electrospun scaffold over film in our adhesion, viability and proliferation assays.…”
Section: Discussionsupporting
confidence: 86%
“…Nanofibrous scaffolds produced by electrospinning have a great 12 potential in many biomedical applications and they are suitable substrates to promote cell attachment, proliferation, and differentiation 19,20 . Electrospun nanofibrous scaffolds possess many unique properties, including extremely high surface-to-volume ratio, appropriate porosity, and malleability to conform to a wide variety of sizes and shapes which are similar to the ECM and can enhance the adhesion, proliferation and growth of cells 2,4 . Previous findings from many other researchers were consistent with ours, which also demonstrated that the nanoarchitecture of the scaffold has significant effects on various cell behaviors including cell adhesion, orientation and proliferation [21][22][23] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations